2020
DOI: 10.2478/acph-2021-0016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential COVID-19 main protease inhibitors using structure-based pharmacophore approach, molecular docking and repurposing studies

Abstract: The current outbreak of novel coronavirus (COVID-19) infections urges the need to identify potential therapeutic agents. Therefore, the repurposing of FDA-approved drugs against today’s diseases involves the use of de-risked compounds with potentially lower costs and shorter development timelines. In this study, the recently resolved X-ray crystallographic structure of COVID-19 main protease (Mpro) was used to generate a pharmacophore model and to conduct a docking study to capture antiviral drugs as new promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 36 publications
(31 reference statements)
1
18
0
Order By: Relevance
“…Further, the structure-based pharmacophore model suggests that vanillin derivatives (1-20) exhibited promising results, and these compounds were suggested to be potent COVID-19 antiviral compounds [157]. Using the X-ray crystallographic structure of COVID-19 main protease (M pro ), Daoud et al (2020) constructed a pharmacophore model and further conducted a molecular docking study to identify antiviral drugs as potential COVID-19 main protease inhibitors. Five FDA-approved antiviral drugs (lopinavir, remdesivir, ritonavir, saquinavir, and raltegravir) were successfully captured by the pharmacophore model, and docking studies revealed that these compounds exhibit many specific binding interactions comparable to that of the cocrystallized inhibitor (X77) [158].…”
Section: Case Study Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the structure-based pharmacophore model suggests that vanillin derivatives (1-20) exhibited promising results, and these compounds were suggested to be potent COVID-19 antiviral compounds [157]. Using the X-ray crystallographic structure of COVID-19 main protease (M pro ), Daoud et al (2020) constructed a pharmacophore model and further conducted a molecular docking study to identify antiviral drugs as potential COVID-19 main protease inhibitors. Five FDA-approved antiviral drugs (lopinavir, remdesivir, ritonavir, saquinavir, and raltegravir) were successfully captured by the pharmacophore model, and docking studies revealed that these compounds exhibit many specific binding interactions comparable to that of the cocrystallized inhibitor (X77) [158].…”
Section: Case Study Of Covid-19mentioning
confidence: 99%
“…Using the X-ray crystallographic structure of COVID-19 main protease (M pro ), Daoud et al (2020) constructed a pharmacophore model and further conducted a molecular docking study to identify antiviral drugs as potential COVID-19 main protease inhibitors. Five FDA-approved antiviral drugs (lopinavir, remdesivir, ritonavir, saquinavir, and raltegravir) were successfully captured by the pharmacophore model, and docking studies revealed that these compounds exhibit many specific binding interactions comparable to that of the cocrystallized inhibitor (X77) [158]. explored the binding potentiality of six approved drugs (chloroquine, hydroxychloroquine, favipiravir, lopinavir, remdesivir, and ritonavir) against fifteen potential drug targets of SARsS-CoV-2 (spike glycoprotein, RNA dependent RNA polymerase, nsp7, nsp8, papain-like protease, main protease, nucleocapsid protein, heptad repeat of domain 2, ADP ribose phosphatase, nsp9 RNA binding protein, endoribonuclease, orf7a, nsp10, and nsp1) using molecular docking and molecular dynamic simulation approach and concluded that out of all the six drugs, ritonavir and lopinavir showed better binding with the prioritized drug targets [159].…”
Section: Case Study Of Covid-19mentioning
confidence: 99%
“…Antivirals which inhibit the RdRP, such as favipiravir, galidesivir, tenofovir, sofobuvir and clevudine have been proposed as COVID-19 repurposing candidates ( Elfiky, 2020 ; Rafi et al, 2020 ; Sultana et al, 2020 ). On the other hand, antivirals inhibiting RNA replication, such as remdesivir and emtricitabine, have shown promising clinical trial outcomes ( Ayerdi et al, 2020 ; Daoud, Alabed, & Dahabiyeh, 2021 ).…”
Section: Drug Repurposing Candidates For Covid-19mentioning
confidence: 99%
“…This information would provide novel insights into drug development to prevent infection and as well as to control transmission [ 141 ]. Several molecular docking, dynamics and pharmacology approaches have been investigated based on the binding affinity of drug components against COVID-19 [ [142] , [143] , [144] ]. Proteomics based directed drug repurposing might be a rapid response solution for the COVID-19 pandemic, based on the experience with SARS-CoV, MERS-CoV, or other coronaviruses.…”
Section: Possibilities Of Harnessing Omics Approaches To Combat Covid-19mentioning
confidence: 99%